Bidirectional associations between short sleep duration, insomnia symptoms, and psychotic-like experiences in adolescents. - Wang, Dongfang; Li, Yuanyuan; Fan, Yunge; Ma, Zijuan; Sun, Meng; Liu, Xianchen; Fan, Fang (European Child & Adolescent Psychiatry, 2025)
This study investigates the prospective associations between short sleep duration, insomnia symptoms, and psychotic-like experiences (PLEs) in a large sample of Chinese adolescents. This study utilized a three-timepoint repeated cross-sectional survey with two nested longitudinal subsamples. A total of 17,722 adolescents were assessed at baseline (April 21 to May 12, 2021) and six months later (December 17 to 26, 2021). Out of these, 15,694 adolescents provided complete responses to the questions at baseline and one year later (May 17 - June 6, 2022). A self-administered questionnaire was used to measure sample characteristics (at baseline), sleep duration, insomnia symptoms, and PLEs (at each assessment), and negative life events (at two follow-ups). Baseline short sleep duration and insomnia symptoms predicted frequent PLEs at both follow-up assessments. Additionally, baseline frequent PLEs also predicted insomnia symptoms at six months and one year later. However, when controlling for confounders, PLEs at baseline only predicted short sleep duration at six months, and not at one year. This study reveals bidirectional prospective relationships between short sleep duration, insomnia symptoms, and PLEs, even after controlling for covariates. Therefore, it is crucial to assess both sleep patterns and PLEs in order to promote optimal sleep and mental health among adolescents.